Pyroptosis in the Initiation and Progression of Atherosclerosis - Qian, Zhengtao; Zhao, Yilin; Wan, Chuandan; Deng, Yimai; Zhuang, Yaoyao; Xu, Yeqiong; Zhu, Yanping; Lu, Shourong; Bao, Zhengyang (Frontiers in Pharmacology, 2021)
Pyroptosis, a newly discovered form of programmed cell death, is characterized by cell swelling, the protrusion of large bubbles from the plasma membrane and cell lysis. This death pathway is mediated by the pore formation of gasdermin D (GSDMD), which is activated by human caspase-1/caspase-4/caspase-5 (or mouse caspase-1/caspase11), and followed with the releasing of both cell contents and proinflammatory cytokines. Pyroptosis was initially found to function as an innate immune effector mechanism to facilitate host defense against pathogenic microorganisms, and subsequent studies revealed that pyroptosis also plays an eventful role in inflammatory immune diseases and tumor resistance. Recent studies have also shown that pyroptosis is involved in the initiation, the progression and complications of atherosclerosis. Here, we provide an overview of the role of pyroptosis in atherosclerosis by focusing on three important participating cells: ECs, macrophages, and SMCs. In addition, we also summarized drugs and stimuli that regulate the progression of atherosclerosis by influencing cell pyroptosis.